Diagnosis Dan Tatalaksana Terkini Retinopati Autoimun : Sebuah Tinjauan Pustaka - Anugrahsari, Santi; Koloay, Gisselle Angeli Marchella; Shendy , Shendy; Prakarsi, Griyanti Purna (Jurnal MedScientiae, 2025)
Autoimmune Retinopathy (AIR) is a rare inflammatory disease that causes progressive vision loss due to an autoimmune response against retinal proteins, primarily those of photoreceptor and bipolar cells. AIR is divided into two main subtypes: Paraneoplastic Retinopathy (Carcinoma-Associated Retinopathy (CAR) and Melanoma-Associated Retinopathy (MAR) and Non-Paraneoplastic Autoimmune Retinopathy (npAIR). Diagnosing Autoimmune Retinopathy remains challenging because no standardized diagnostic criteria exist. Essential diagnostic criteria include visual dysfunction, electroretinogram abnormalities, the presence of anti-retinal antibodies, the absence of fundus lesions, and the absence of intraocular inflammation. Currently, no evidence-based standard treatment protocol exists; however, immunosuppressive interventions such as systemic steroids, steroid-sparing agents, local therapy, and biologic agents have been used to slow disease progression. This study is a literature review that aims to examine the current diagnosis and management aspects of Autoimmune Retinopathy, based on 11 scientific articles selected from the Google Scholar and PubMed databases, using recent inclusion criteria (2020–2025). Autoimmune retinopathy is a disease with a multifactorial immunopathological mechanism involving humoral and cellular immunity. Early diagnosis, close monitoring of retinal function, and appropriate selection of immunosuppressive therapy are key to preventing further retinal damage. The results of this review are expected to provide comprehensive guidance and identify knowledge gaps for future AIR management.